Leadership-Focused Coaching in Action: An Approach to Continuous Improvement and Supporting Public Schools - Gray, Julie A.; Walker, Aneta; Zimmerman, Sherri; Dickson, James (International Journal of Education Policy and Leadership, 2022)
This article details the efforts of one program’s collaborative efforts toward continuous improvement and strengthening partnerships with local school districts using Leadership-Focused Coaching, a research-based model for principal preparation programs. Practical experiences and lessons learned from the ongoing online program improvement and redesign initiative are shared. In advance of two accreditation visits, data and feedback were gathered from partner districts, recent graduates, current students, and employers, which helped to identify ways in which the program could better prepare instructional leaders. This article describes the efforts, successes, setbacks, and future plans of a group of professors working to improve a program while preparing for accreditation visits and strengthening district partnerships.